Gemcitabine-induced coronary vasospasm: A case report - Mahmut Tuna Katırcıbaşı; Aynur Eken (KARE Publishing, 2017)
Gemcitabine is a chemotherapy drug. It is a nucleoside analogue that is usually well tolerated by patients, with myelosuppression (especially thrombocytopenia) as dose-limiting side effect. Other mild to moderate side effects include alopecia, vomiting, nausea, rash, and fever. Coronary ischemia is the most common cardiotoxic effect of gemcitabine, which is due to its antimetabolites. While underlying cause of coronary ischemia following use of gemcitabine is uncertain, endothelial dysfunction and coronary thrombosis are potential explanations. To our knowledge, there are few published case reports of adverse cardiovascular side effects associated with gemcitabine. Presently described is case of acute inferior myocardial infarction in a female patient caused by gemcitabine.